Cohort Profile Update: The Norwegian Mother and Child Cohort Study (MoBa) - Magnus, Per; Birke, Charlotte; Vejrup, Kristine; Haugan, Anita; Alsaker, Elin; Daltveit, Anne Kjersti; Handal, Marte; Haugen, Margaretha; Høiseth, Gudrun; Knudsen, Gun Peggy; Paltiel, Liv; Schreuder, Patricia; et al. (International journal of epidemiology, 2016)
This is an update of the Norwegian Mother and Child Cohort Study (MoBa) cohort profile which was published in 2006. Pregnant women attending a routine ultrasound examination were initially invited. The first child was born in October 1999 and the last in July 2009. The participation rate was 41%. The cohort includes more than 114 000 children, 95 000 mothers and 75 000 fathers. About 1900 pairs of twins have been born. There are approximately 16 400 women who participate with more than one pregnancy. Blood samples were obtained from both parents during pregnancy and from mothers and children (umbilical cord) after birth. Samples of DNA, RNA, whole blood, plasma and urine are stored in a biobank. During pregnancy, the mother responded to three questionnaires and the father to one. After birth, questionnaires were sent out when the child was 6 months, 18 months and 3 years old. Several sub-projects have selected participants for in-depth clinical assessment and exposure measures. The purpose of this update is to explain and describe new additions to the data collection, including questionnaires at 5, 7, 8 and 13 years as well as linkages to health registries, and to point to some findings and new areas of research. Further information can be found at [www.fhi.no/moba-en]. Researchers interested in collaboration and access to the data can complete an electronic application available on the MoBa website above.